Children's explorations of the concept of spinning in preschool: Science learning in mediated activity. (June 2018) - Samuelsson, Robin
Abstract: This paper examines how children explore the concept of spinning during a preschool project. It takes a cultural-historical approach, and analyzes how artifacts can be used in development of abstract concepts. In line with the pedagogical goals teachers employ these in learning activities during the project in line with their pedagogical goals. Children encounter the activities with different linguistic and perceptual means; there is, however, across the project a shift towards learning activities that promote verbal explanations. The interrelation of verbal and perceptual means, suggest ways in how children dynamically develop abstract concepts out of perceptual knowledge in activities with appropriate artifacts and teacher scaffolding.